Influence of external pressure on conductivity of systems based on polyethylene oxide and carbon nanotubes - Lysenkov, E.A.; Klepko, V.V. (Functional Materials, 2016)
Features of conductivity of systems based on polyethylene oxide and carbon nanotubes depending on the value of external pressure are studied using method of impedance spectroscopy. It is revealed that dependence of conductivity on pressure shows percolation behavior. The mechanisms of nonlinear change of conductivity with the pressure increase are described and a scheme for their explanation is offered. It is shown that the investigated systems are perspective piezoresistive materials.